Algal flora of Madhabkunda waterfall area in Maulvi Bazar, Bangladesh. III. New records of blue-greens and greens - Aziz, Abdul (Bangladesh Journal of Botany, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Examination of samples from Madhabkunda waterfall area at Maulvi Bazar, Bangladesh revealed the presence of Aphanocapsa montana Cramer, Oscillatoria acuiformis Skuja, Oscillatoria redeckii Van Goor, Gloeotrichia natans (Hedwig) Rabenh., Nostochopsis lobatus Wood em Geitler, Schizochlamys gelatinosa A. Br. and Kirchneriella dianae (Bohl.) Coms var. dianae Bohl., Oscillatoria redeckii Van Goor is a new records for this Subcontinent. Aphanocapsa montana Cramer, Oscillatoria acuiformis Skuja, Nostochopsis lobatus Wood em Geitler and Kirchneriella dianae (Bohl.) Coms var. dianae Bohl. are new records for Bangladesh. Key words: Blue-green algae, Cyanobacteria, Green algae, Waterfall, Bangladesh doi:10.3329/bjb.v37i1.1562 Bangladesh J. Bot. 37(1): 43-48, 2008 (June)